The Construction and Approximation of the Neural Network with Two Weights - Zhiyong Quan; Zhengqiu Zhang (Journal of Applied Mathematics)
The technique of approximate partition of unity, the way of Fourier series, and inequality technique are used to construct a neural network with two weights and with sigmoidal functions. Furthermore by using inequality technique, we prove that the neural network with two weights can more precisely approximate any nonlinear continuous function than BP neural network constructed in (Chen et al., 2012).